The Influence of Work Facilities, Work Discipline and Leadership Style on Employee Performance - Fira, Lisa; Rumengan, Muhammad Tammy Ikbal (Zona Manajerial: Program Studi Manajemen (S1), 2022)
The purpose of this research were to find out influence of work facilities, work discipline and leadership style affect employee performance of PT. Taman Nongsa Indah Village either partially or simultaneously. The population in this study were all employees of the Department of Trade Semarang were 56 employees. This research is saturated sampling. The type of data used is primary data. Methods of data collection using questionnaires, documentation, observation and interviews. The test technique used is validity test, reliability test, classical assumption test including normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing in this study uses multiple linear regression analysis and hypothesis testing with the help of SPSS. The results of this study indicate that work facilities variable has no significant effect, but has a positive direction of influence on employee performance at PT. Nongsa Indah Village, work discipline has a positive and significant effect on employee performance at PT. Taman Nongsa Indah Village, Leadership style has no significant effect but has positive direction of influence on employee performance at PT. Taman Nongsa Indah Village.